Cover Feature: Dendritic Fibrous Nanosilica for Catalysis, Energy Harvesting, Carbon Dioxide Mitigation, Drug Delivery, and Sensing (ChemSusChem 20/2017). Issue 20 (12th October 2017) - Maity, Ayan; Polshettiwar, Vivek
Abstract : The Cover Feature shows technologies in the fields of energy, environment, and health in which morphology‐controlled nanomaterials such as silica could play a crucial role. Nanosilicas can be synthesized and designed with a large variety of sizes, shapes, morphologies, and textural properties (surface area, pore size and pore volume) to meet the challenges of the fields. One notable material is the dendritic fibrous nanosilica. This material has a unique fibrous morphology and a high surface area with improved accessibility to the internal surface, tunable pore size and volume, controllable particle size, and importantly, which makes it useful for a variety of applications. More information can be found in the Review by Maity and Polshettiwar onpage 3866 in Issue 20, 2017 (DOI:10.1002/cssc.201701076 ).